Native Cultural Competency in Mainstream Schooling "Outsider" Teachers with Insider Knowledge - Williams, Sharon Vegh (Springer International Publishing, 2018)
This book provides an in-depth analysis of Native American educational issues in the Northeast and highlights teacher training and instruction that address the experience and needs of the many Native students that attend reservation border town schools. Williams and Cole expand upon the results of a participatory action study that explored the barriers to success for Native American students in mainstream schooling during the process of creating and implementing a Native cultural competency teacher-training program for classroom teachers. They document the evolution of cross-cultural relationships and interactions in a diverse schooling context and aim to usher in concrete changes in school experiences and educational outcomes for Native American students by fostering non-Native teachers' growth in cultural competency.